Toxicology of metals and metalloids - Barbosa Jr, Fernando (2014)
Metal toxicology is one of the oldest areas of study of toxicology and one of the oldest environmental problems. Metals and metalloids are toxic elements at the top of the priority list of hazardous substances of the Agency for Toxic Substances and Disease Registry (ATSDR). However, several gaps of knowledge still exist that are related to their toxicity, mainly concerning the mechanisms of action. This special issue affords the opportunity to bring together the results of nine papers covering several aspects of the toxicology of metals and metalloids in in vitro and in vivo experimental models, as well as in exposed populations.